IoT-Based Smart Management of Off-Grid Photovoltaic Systems in Rural and Remote Settings - Ishimwe, Viviane; Mongilli, Mirco; Rukundo, Eraste; Matrella, Guido; Ciampolini, Paolo (2024 IEEE PES/IAS PowerAfrica, 2024)
Renewable energy sources have demonstrated their dependability and are widely acknowledged as the optimal choice for meeting the growing demand for energy while mitigating the impacts of climate change. Inexpensive photovoltaic systems are often adopted to provide affordable access to electricity in rural settings. However, poor maintenance and control of such systems may jeopardize their effectiveness, possibly leading to the electric power disruption seen in many solar PV use cases. This study highlights an Internet of Things (IoT)-based strategy for the efficient usage and management of off-grid solar installations in rural and remote locations. Beyond the main purpose of remote control and fault prevention, the system accounts for a much wider and more flexible architecture, also suitable for monitoring many different applications, thus promoting the effective use of energy. The system is being developed in the framework of a European Erasmus+ Project, aiming at capacity building and involving four Rwandan Universities. A set of demonstration facilities called Living Labs aimed at different use cases, are going to be deployed. A demo system has been designed, implemented, and tested as a proof of concept, accounting for all field-distributed and cloud-based components. Preliminary results are shown, illustrating the system's functionality.